2017
DOI: 10.1111/jocn.13916
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination timeliness in preterm infants: An integrative review of the literature

Abstract: Care providers should acknowledge the risk of a delay in preterm infants and actively promote vaccination in this population. Regular training should help to negate the occurrence of inappropriate delays, and careful discharge planning is needed to ensure that preterm infants are vaccinated on time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 29 publications
4
10
2
1
Order By: Relevance
“…In conclusion, our results support the current ACIP recommendations to administer the first dose of measles-containing vaccine at age 12 through 15 months for all children, including those born preterm [1,13,31]. Delaying vaccination of measles-containing vaccines may increase the risk of seizures following vaccination.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In conclusion, our results support the current ACIP recommendations to administer the first dose of measles-containing vaccine at age 12 through 15 months for all children, including those born preterm [1,13,31]. Delaying vaccination of measles-containing vaccines may increase the risk of seizures following vaccination.…”
Section: Discussionsupporting
confidence: 83%
“…Additionally, differences in the underlying medical conditions or health-seeking behaviors may exist between those who are vaccinated at the recommended age versus those who receive it later [6]. Parents of preterm infants may delay MMR vaccination for their child [13,14], as the incidence of febrile seizures is higher in children who are born preterm than those born full-term [1517]. However, data concerning the safety of vaccination in children born preterm compared to children born full-term is limited particularly for vaccinations received during the second year of life [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…16 Another study suggests, as we did, that initiating vaccination in the hospital setting was associated with future vaccination, 38 leading some to speculate that this helped to alleviate parent and provider vaccine safety concerns and helped to instill confidence in vaccinating high-risk infants after hospital discharge. 39 Earlier work has also indicated that parents and providers may have limited knowledge of and adherence to vaccine recommendations for preterm infants. 15,34,[40][41][42][43] One study revealed that less than half of parents knew that preterm infants should be vaccinated at the same age as term infants, 40% thought the extent of prematurity influenced timing of vaccination, and 25% believed a minimum weight needed to be reached before vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, not only do preterm newborns have immunologic immaturities, but they are deprived of maternal antibodies. The risk of delay in vaccine administration is high and increases with decreasing gestational age at birth [88]. Given their higher vulnerability, preterm infants also benefit from influenza vaccine (as of 6 months of age) and passive immunization against respiratory syncytial virus (RSV).…”
Section: Protecting the Most Vulnerable: How Intensive Care Physicianmentioning
confidence: 99%